2020
DOI: 10.1007/s10029-020-02315-2
|View full text |Cite
|
Sign up to set email alerts
|

Tissue remodeling macrophages morphologically dominate at the interface of polypropylene surgical meshes in the human abdomen

Abstract: Background Mesh implants are widely used to reinforce the abdominal wall, although the inevitable inflammatory foreign body reaction (FBR) at the interface leads to complications. Macrophages are suspected to regulate the subsequent scar formation, but it is still unclear whether adequate fibrous scar formation with collagen deposition depends mainly on the presence of M1 or M2 macrophages. Methods This study investigated the FBR to seven human polypropylene meshes, which were removed after a median incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…The data are presented as mean (SE). Significant differences between zones according to Mann-Whitney U test: a zone1 and zone2, b zone1 and zone6 Parameter (n = 7 PP meshes) Distance from mesh fibers previous studies of the same specimens that clearly showed excessive collagen deposition [20], may suggest T regs are not antifibrotic in our samples. Within the FBGs, CD20 + B cells were rare at about 5%, which is in agreement with several studies [4,23,27], but interestingly dense clusters were frequently found near the FBGs accumulated around blood vessels.…”
Section: Discussionmentioning
confidence: 68%
“…The data are presented as mean (SE). Significant differences between zones according to Mann-Whitney U test: a zone1 and zone2, b zone1 and zone6 Parameter (n = 7 PP meshes) Distance from mesh fibers previous studies of the same specimens that clearly showed excessive collagen deposition [20], may suggest T regs are not antifibrotic in our samples. Within the FBGs, CD20 + B cells were rare at about 5%, which is in agreement with several studies [4,23,27], but interestingly dense clusters were frequently found near the FBGs accumulated around blood vessels.…”
Section: Discussionmentioning
confidence: 68%
“…As already indicated by the previous work of Dievernich et al using double stainings, only a minority of cells that just expressed a single marker can be assigned to a specific cell type ( 1 ). As we restricted the analyses just to the inflammatory infiltrate of the granuloma in this study, we did not look for spatial gradients.…”
Section: Resultsmentioning
confidence: 79%
“…Macrophages have been shown to be the predominant actors of the chronic inflammation around these foreign bodies, with some of them fusing to multinucleated foreign body giant cells (FBGCs) ( Supplementary Figure 1A in Supplementary Material 1 ). Characteristic surface markers are CD68 as pan-macrophage marker, CD86 for M1 subtype, CD105 indicates macrophage activation, and CD163 and also CD206 reflect M2 subtypes ( 1 ). Though these subtypes appear with distinct spatial distribution, they all can be found within a FBG.…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of the present study and those of Gruber-Blum et al . 24 did not show significant differences between groups with or without an anti-adhesive barrier in relation to the intensity of the foreign body reaction, although there was a greater tendency to it in the polypropylene/polyglecaprone mesh group.…”
Section: Discussionmentioning
confidence: 60%
“…Despite the 21 postoperative days, large fragments of the polyglecaprone barriers remained, surrounded by clusters of macrophages and giant foreign body cells. The use of synthetic meshes for the repair of defects in the abdominal wall, especially tissue separating meshes, implies a greater amount of degradable synthetic or biological polymers that determine an inflammatory response accompanied by a greater number of macrophages M1 and M2 and giant cells capable of leading to the biodegradation of this absorbable material and the involvement of the nonabsorbable filaments of the mesh, during the process of fibroplasia, incorporating the mesh to the tissue 24 .…”
Section: Discussionmentioning
confidence: 99%